Criminal Careers, Criminal Violence, and Substance Abuse in California, 1963-1983 - Wenk, Ernst ([Verlag nicht ermittelbar], 1998)
The purpose of the study was to investigate the criminal career patterns of violent offenders. These data are intended to facilitate the development of models to predict recidivism and violence, and to construct parole supervision programs. Original data were collected on young male offenders in 1964 and 1965 as they entered the California Youth Authority (CYA). At this time, data were collected on criminal history, including current offenses, drug and alcohol use, psychological and personality variables, and sentencing, and demographics such as age, education, work experience, and family structure. The data collection also contains results from a number of standardized psychological instruments: California Psychological Inventory, Minnesota Multiphasic Personality Inventory, California Achievement Test Battery, General Aptitude Test Battery, Army General Classification Test, and the Revised Beta Test. After release from the CYA and over the following 20 years, subsequent arrest information was collected on the offenders, including the nature of the offense, disposition, and arrest and parole dates.